DEVELOPMENT OF INTERACTIVE LEARNING MEDIA USING ADOBE FLASH CS6 FOR DIGITAL SIMULATION SUBJECTS: AN ADDIE-BASED DESIGN STUDY - Mohammad Irfan Ali Fahroni; Anggara Sukma Adiyanta (JoEICT (Jurnal of Education And ICT), 2026)
The integration of technology in education has intensified the demand for engaging, interactive instructional resources. Despite this, many vocational high schools in Indonesia continue to rely on static, text-based materials that fail to meet the learning needs of twenty-first-century students. This study addresses the identified gap by developing an interactive learning medium for the Digital Simulation (SIMDIG) subject—specifically focused on Microsoft Excel statistical functions—using Adobe Flash CS6 at SMK Negeri 2 Tulungagung. The development followed the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, which provides a systematic and iterative framework for instructional design. The needs-analysis phase employed structured observation and semi-structured interviews, revealing an over-reliance on printed handouts and PowerPoint presentations with limited interactive features. The designed medium incorporates animated explanations, an interactive evaluative component, and a navigable menu structure. Validity was assessed through expert reviews: the media expert awarded a feasibility score of 80% (Feasible), and the content expert assigned 85% (Highly Feasible). User-acceptability trials yielded 85% in a small-group trial (n = 5) and 84% in a large-group trial (n = 15), both classified as Highly Feasible. These findings suggest that the Adobe Flash-based medium effectively satisfies both technical and pedagogical quality standards, offering a replicable model for interactive media development in vocational education contexts. Future research should investigate its direct impact on student learning outcomes and extend its applicability to other SIMDIG topics.